Adaptive Fault-Tolerant Communication Based-Control for Parallel Connected Rectifiers - Ali Sharida (17947847) (2023)
This article proposes an adaptive and fault-tolerant communication method for controlling parallel-connected active front-end rectifiers (AFRs). The proposed method relies on the principle of master-slave communication based on the controller area network bus protocol. The master unit is responsible for generating current reference signal and for sharing it with the slaves, while the slave units are solely responsible for generating the power based on the received reference set points. The master can be selected and changed automatically based on a negotiation algorithm among the connected rectifiers. Then, if a communication fault occurs in the master, another master is chosen by the slaves. On the other hand, slaves’ communication faults are tolerated by switching to communication-less mode of operation with online estimation of the current reference signal instead of receiving it over the communication network. The proposed algorithms are validated by simulation and experimentally on a prototype with three parallel AFRs. Other Information Published in: IEEE Open Journal of the Industrial Electronics Society License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/ojies.2023.3342071